Patients with venous thromboembolism after spontaneous intracerebral hemorrhage: a review - Qiyan Cai (BMC, 2021)
Abstract Background Patients with spontaneous intracerebral hemorrhage (ICH) have a higher risk of venous thromboembolism (VTE) and in-hospital VTE is independently associated with poor outcomes for this patient population. Methods A comprehensive literature search about patients with VTE after spontaneous ICH was conducted using databases MEDLINE and PubMed. We searched for the following terms and other related terms (in US and UK spelling) to identify relevant studies: intracerebral hemorrhage, ICH, intraparenchymal hemorrhage, IPH, venous thromboembolism, VTE, deep vein thrombosis, DVT, pulmonary embolism, and PE. The search was restricted to human subjects and limited to articles published in English. Abstracts were screened and data from potentially relevant articles was analyzed. Results The prophylaxis and treatment of VTE are of vital importance for patients with spontaneous ICH. Prophylaxis measures can be mainly categorized into mechanical prophylaxis and chemoprophylaxis. Treatment strategies include anticoagulation, vena cava filter, systemic thrombolytic therapy, catheter-based thrombus removal, and surgical embolectomy. We briefly summarized the state of knowledge regarding the prophylaxis measures and treatment strategies of VTE after spontaneous ICH in this review, especially on chemoprophylaxis and anticoagulation therapy. Early mechanical prophylaxis, especially with intermittent pneumatic compression, is recommended by recent guidelines for patients with spontaneous ICH. While decision-making on chemoprophylaxis and anticoagulation therapy evokes debate among clinicians, because of the concern that anticoagulants may increase the risk of recurrent ICH and hematoma expansion. Uncertainty still exists regarding optimal anticoagulants, the timing of initiation, and dosage. Conclusion Based on current evidence, we deem that initiating chemoprophylaxis with UFH/LMWH within 24–48 h of ICH onset could be safe; anticoagulation therapy should depend on individual clinical condition; the role of NOACs in this patient population could be promising.